2020
DOI: 10.3389/fcimb.2020.00277
|View full text |Cite
|
Sign up to set email alerts
|

Rhinovirus and Innate Immune Function of Airway Epithelium

Abstract: Airway epithelial cells, which lines the respiratory mucosa is in direct contact with the environment. Airway epithelial cells are the primary target for rhinovirus and other inhaled pathogens. In response to rhinovirus infection, airway epithelial cells mount both pro-inflammatory responses and antiviral innate immune responses to clear the virus efficiently. Some of the antiviral responses include the expression of IFNs, endoplasmic reticulum stress induced unfolded protein response and autophagy. Airway epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 164 publications
0
23
0
1
Order By: Relevance
“…This focus was based on the observation that wheezing in association with HRV infection is a risk factor for AA. 36,37 The TLR-IRF-IFN pathway (Fig 5 , B, top) plays a role in HRV immunity, 38,39 and deficiencies along this pathway (including TLR7) have been linked to AA risk and/or severity. [40][41][42][43] We found that several HRV-associated TLRs (TLR2/7/8), IRFs (IRF7/9), signaling mediators (MYD88), sensors (IFIH1, DDX58), and downstream effectors (STAT1, STAT2), as well as a gene signature of IFN-stimulated genes (ISG; used as a proxy for type I IFN levels 44 ), had lower expression in the maladaptive versus adaptive and resilient phenotypes (Fig 5 E7 and E8).…”
Section: Maladaptive Phenotype and Aa Risk: Shared Molecular Determinants In Peripheral Bloodmentioning
confidence: 99%
“…This focus was based on the observation that wheezing in association with HRV infection is a risk factor for AA. 36,37 The TLR-IRF-IFN pathway (Fig 5 , B, top) plays a role in HRV immunity, 38,39 and deficiencies along this pathway (including TLR7) have been linked to AA risk and/or severity. [40][41][42][43] We found that several HRV-associated TLRs (TLR2/7/8), IRFs (IRF7/9), signaling mediators (MYD88), sensors (IFIH1, DDX58), and downstream effectors (STAT1, STAT2), as well as a gene signature of IFN-stimulated genes (ISG; used as a proxy for type I IFN levels 44 ), had lower expression in the maladaptive versus adaptive and resilient phenotypes (Fig 5 E7 and E8).…”
Section: Maladaptive Phenotype and Aa Risk: Shared Molecular Determinants In Peripheral Bloodmentioning
confidence: 99%
“…In asthma, RV-induced exacerbations are a major cause of disease morbidity and mortality, and increasing healthcare costs 30 . Airway epithelial cells, the primary target of respiratory viruses such as RV, can mount both inflammatory and antiviral innate immune responses aimed to efficiently clear the virus 31 . In our previous study, we provided the first evidence that RV infection in human primary airway epithelial cell culture and mouse models induces the expression of IP and this induction enhances the host antiviral mechanism 9 .…”
Section: Discussionmentioning
confidence: 99%
“…After entering endosomes, TLR 3 and TLR 7/8 bind to double-and single-stranded RNA, respectively. Interactions with these TLRs trigger activation of the NF-κB pathway and increase production of interferon (IFN)-β, IFN-γ, IL-6, and IL-8 ( Jacobs et al, 2013 ; Makris and Johnston, 2018 ; Ganjian et al, 2020 ). Geng et al reported that kakkonto treatment decreases the mRNA and protein levels of TLR7 and myeloid differentiation primary response 88 in murine lung tissues infected with H1N1 influenza virus, indicating that kakkonto exerts an inhibitory effect on activation of the NF-κB pathway ( Geng et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%